Exercise interventions for dementia and cognitive impairment: The Seattle Protocols - Linda Teri; Rebecca G. Logsdon; Susan M. McCurry (2008)
Research evidence strongly suggests that increased physical exercise may not only improve physical function in older adults but may also improve mood and slow the progression of cognitive decline. This paper describes a series of evidence-based interventions grounded in social-learning and gerontological theory that were designed to increase physical activity in persons with dementia and mild cognitive impairment. These programs, part of a collective termed the Seattle Protocols, are systematic, evidence-based approaches that are unique 1) in their focus on the importance of making regular exercise a pleasant activity, and 2) in teaching both cognitively impaired participants and their caregivers behavioral and problem-solving strategies for successfully establishing and maintaining realistic and pleasant exercise goals. While additional research is needed, initial findings from randomized controlled clinical trials are quite promising and suggest that the Seattle Protocols are both feasible and beneficial for community-residing individuals with a range of cognitive abilities and impairments.